Assessment of the Ability to Relate Anterior Tooth Form and Arrangement to Gender - Jasse, Fernanda Ferreira [UNESP]; Correa, Josiane Vilhena; Santos da Cruz, Andrea Ferreira; Pantoja Fontelles, Mauro Jose; Roberto, Andiara Ribeiro [UNESP]; Cury Saad, Jose Roberto [UNESP]; Campos, Edson Alves de [UNESP] (Wiley-Blackwell, 2012)
Purpose: This study evaluated the assumption that there are morphological differences between the natural anterior dentition of men and women. The goal of the study was to determine the gender of patients based on the appearance of the anterior teeth in photographs. Materials and Methods: Laymen and observers from different specialties were asked to determine the gender of individuals based on the shape and arrangement of anterior teeth. Forty anterior dentition photographs of dental students of both genders (20 women, 20 men) between 18 and 26 years old were selected, coded, and randomly arranged in an album. The albums were delivered to five groups of observers: general practitioners (recently graduated dentists), prosthodontists, orthodontists, restorative dentists (specialists in cosmetic and restorative dentistry), and laymen (control group). The observers evaluated the photographs twice at 1-week intervals. Results: The average correctly identified values in women and men were 57.6% and 58.8%, respectively. There was no statistical difference between observers and between each group of professionals and the laymen group (p > 0.05). An intraobserver agreement was not observed between the evaluations (kappa =-0.01). Conclusion: The results of this limited study indicated that it was not possible to differentiate gender by viewing photographs of anterior teeth.
Keywords: Esthetics; tooth shape; dentogenic theory